2017
DOI: 10.1038/ijo.2017.124
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of obese individuals before and after a one year weight loss program

Abstract: Diet-induced weight loss leads to mainly reduced levels of metabolites that are elevated in obese insulin resistant individuals. We identified multiple new associations with metabolic risk factors and validated several previous findings related to weight loss-mediated metabolite changes. Levels of specific metabolites, such as xylitol, may be predictive of the response to non-surgical weight loss already at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
4
43
0
4
Order By: Relevance
“…The second block includes five studies focused on studying the differential responses of obese and non-obese subjects to dietary challenges (Table 2 ) (Badoud et al 2015b ; Baker et al 2015 ; Geidenstam et al 2014 ; Bak et al 2018 ). The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second block includes five studies focused on studying the differential responses of obese and non-obese subjects to dietary challenges (Table 2 ) (Badoud et al 2015b ; Baker et al 2015 ; Geidenstam et al 2014 ; Bak et al 2018 ). The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Geidenstam et al ( 2017a ) identified changes in the plasma levels of several AAs after weight loss for nine months and weight maintenance in obese subjects and evaluated in a replication cohort (Table 2 ). Of the 21 detected AAs, only tyrosine approached the lean reference profile (no initial increase) after weight loss, and this profile was maintained after weight maintenance (Geidenstam et al 2017a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Geidenstam et al reported that baseline levels of serum xylitol showed an inverse association with a ≥10% weight loss in obese subjects fed low-calorie diet [ 37 ]. Firmicutes phylum accelerates degradation of food component to supply energy to host, it is, therefore, known as obesity-related bacterial phylum [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical practice of modern Chinese medicine has found that WLS has the effect on reducing weight and fat. Additionally, recent studies have found significant changes in plasma metabolite profiles in obese patients, including increased levels of all branched‐chain amino acids (BCAAs; valine, leucine, and isoleucine) and downstream BCAA metabolites , such as branched‐chain keto acids and short‐chain acylcarnitines as well as glycerol and glycerophosphocholines , which are related to fluid imbalance. However, the effect of WLS on the regulation of body fluid‐plasma metabolism has not been defined.…”
Section: Introductionmentioning
confidence: 99%